The Influence of Working Capital and Sales Growth on Net Profit at PT Sido Muncul Tbk (Case Study on the Indonesian Stock Exchange for the 2018-2023 Period) - Neng Anis Safitri; Yuyun Yuniati Yuningsih (PT FORMOSA CENDEKIA GLOBAL, 2024)
Working capital is a tool to measure a company's ability to create value for investors through the profits it produces. Net profit is a ratio to determine the amount of net profit that has been obtained by the company. Based on this, the author gave the title of this research, namely: